Pengaruh Ekspektasi Pendapatan dan Pemahaman Akuntansi terhadap Minat Berwirausaha Mahasiswa - Sri Ayem; Milanda Milanda (Universitas Batanghari Jambi, 2023)
This study aims to examine the effect of income expectations and understanding of accounting on students entrepreneurial interest, and to test whether Tri N’s teaching moderates the relationship. The researtch was conducted on accounting study program students at univesities in Yogyakarta. Research data obtained through the distribution of questionnaires. The samples in this study were processed using the slovin formula which resulted in 440 samples. Research data using spss with multiple linear regression and Moderated Regression Analiysis (MRA). The hypothesis testing method uses a significant level of 5%. The results of this study indicate that income expectations have a positive effect on student entrepreneurship interest. Accounting understanding has a positive effect on student entrepreneurship interest. The Tri N teachings can strengthen income expectations and understanding of accounting on students interest in entrepreneurship.